Derivational Suffixes Forming Adjectives and Their Syntactic Functions in reference to Hans Christian Andersen's Fairy Tales - Karang, Ni Putu Dinda Nata Pramesti; Ketut Artawa; Ni Luh Nyoman Seri Malini (Journal of Language and Literature Studies, 2024)
Fairy tales can be used as the medium to comprehend the word formation using the derivational suffixes and the word structure using syntactic functions. Furthermore, adjectives are an important class words needed to create a descriptive text that is required in English task, test, or daily use. This research was conducted to identify the types of derivational suffixes that form adjectives and analyze the syntactic functions of derived words. Therefore, the present study is categorized as a qualitative study. The data were obtained from a book titled ‘The Snow Princess and Other Tales’ written by Hans Christian Andersen. The data were gathered using observation and note-taking techniques. The collected data were analyzed by using a descriptive qualitative technique. This research applied an informal method to present the data analysis. The findings of this research revealed that all twelves of the derivational suffixes to form adjective are found in the source. Suffix -al, -ate, -ish, -able, and -less form adjective from noun, suffix -ing, -ise/ize, -ive, -able, and -ing form adjective from verb, and suffix -ish and -ly form adjective and adverb from adjective. Meanwhile, for the syntactic functions the derived words can be functioned as the object, complement, and adverbial element; however, the function as subject and predicator. The result showed that fairy tales are able to help English learners to gain adjectives and its structure in a sentence.